KRITIK TERHADAP HADITS TENTANG FADHILAH SURAT AL-WAQI’AH DALAM KITAB TAFSIR IBN KATSIR - Haerudin, Usep Malik (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This article aims to find out the criticism of the Fadhilah hadith of Al-Waqiah in the commentary of Ibn Katsir. This article aims to find out the validity of the hadith about the fadhilah of Al-Waqiah's letter in the commentary of Ibn Katsir. The method used in this study is descriptive qualitative, with data collection techniques based on library research. Specifically, this method is a method used in research as a critique and review of the literature, especially those related to research themes. Then because this research examines a topic, namely the hadiths about the fadhilah of Surat al-Waqia'h contained in the book of Tafsir al-Qur'anul'Azhim or better known as the commentary of ibn Katsir. The results of the study showed that Ibn Kathir used the tahlili method, which intends to explain the content of the verses of the Qur'an and all its aspects. The tahlili method is explaining the verses of the Qur'an from various aspects based on the sequence of verses and letters in the manuscript. by emphasizing the content of its lafadz-lafadz, its munasabat both between surahs and between verses, asbab al-nuzul, hadiths of the prophet, atsar of the companions and the opinions of the tabi'in related to his arguments. As for the results of the author's research, it can be concluded that the hadiths about the fadhilah of sura Al-Waqi'ah in the commentary of Ibn Katsir, based on the muhadditsin's comments that the hadiths about the primacy of surah al-Waqi'ah are the history of the sanads of mudtarib, majhul, munqathi'. Likewise according to Imam Ahmad, Abu Hatim, al-Daaruquthni, al-Baihaqi, and Ibnul Jauzi. In summary, this hadith is flawed so that it is not authentic. Likewise according to Imam Ahmad, Abu Hatim, al-Daaruquthni, al-Baihaqi, and Ibnul Jauzi. In summary, this hadith is flawed so that it is not authentic.